Leptin Promotes Expression of EMT-Related Transcription Factors and Invasion in a Src and FAK-Dependent Pathway in MCF10A Mammary Epithelial Cells - Monserrat Olea-Flores; Miriam Zuñiga-Eulogio; Arvey Tacuba-Saavedra; Magdalena Bueno-Salgado; Andrea Sánchez-Carvajal; Yovani Vargas-Santiago; Miguel A. Mendoza-Catalán; Eduardo Pérez Salazar; Alejandra García-Hernández; Teresita Padilla-Benavides; Napoleón Navarro-Tito (Cells, 2019)
Leptin is one of the main adipokines secreted in breast tissue. Leptin promotes epithelial−mesenchymal transition (EMT), cell migration and invasion in epithelial breast cells, leading to tumor progression. Although, the molecular mechanisms that underlie these events are not fully understood, the activation of different signaling pathways appears to be essential. In this sense, the effects of leptin on the activation of kinases like Src and FAK, which regulate signaling pathways that activate the EMT program, are not completely described. Therefore, we investigated the involvement of these kinases using an in vitro model for leptin-induced EMT process in the non-tumorigenic MCF10A cell line. To this end, MCF10A cells were stimulated with leptin, and Src and FAK activation was assessed. Specific events occurring during EMT were also evaluated in the presence or absence of the kinases’ chemical inhibitors PP2 and PF-573228. For instance, we tested the expression and subcellular localization of the EMT-related transcription factors Twist and β-catenin, by western blot and immunofluorescence. We also evaluated the secretion and activation of matrix metalloproteases (MMP-2 and MMP-9) by gelatin zymography. Invasiveness properties of leptin-stimulated cells were determined by invadopodia formation assays, and by the Transwell chamber method. Our results showed that leptin promotes EMT through Src and FAK activation, which leads to the secretion and activation of MMP-2 and MMP-9, invadopodia formation and cell invasion in MCF10A cells. In conclusion, our data suggest that leptin promotes an increase in the expression levels of Twist and β-catenin, the secretion of MMP-2, MMP-9, the invadopodia formation and invasion in MCF10A cells in a Src and FAK-dependent manner.